2017
DOI: 10.1002/adem.201600743
|View full text |Cite
|
Sign up to set email alerts
|

Powder Metallurgy Strategies to Improve Properties and Processing of Titanium Alloys: A Review

Abstract: Powder metallurgy (PM) is an attractive technology for manufacturing net-shape titanium-based components. However, it is challenging to make PM titanium products competitive in terms of mechanical properties. This article gives an overview of the current challenges in PM titanium and the best strategies to overcome them by alloying. By adding suitable alloying elements the properties of PM titanium components can be enhanced. The use of sintering aids helps to control the typical residual porosity of PM titani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 80 publications
(119 reference statements)
1
27
0
3
Order By: Relevance
“…Aerospace and biomedical are currently the most important fields for applications of titanium products. Ti-based components are typically manufactured by a multi-step process of vacuum arc melting, hot rolling, scale removal, vacuum annealing machining, and surface treatment; all these fabrication stages make the final product expensive [1][2][3]. Powder metallurgy (PM) processing offers an interesting alternative for many applications since it provides near-net-shape parts [1], enhancing the flexibility of design, minimizing the machining steps, and increasing the material yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerospace and biomedical are currently the most important fields for applications of titanium products. Ti-based components are typically manufactured by a multi-step process of vacuum arc melting, hot rolling, scale removal, vacuum annealing machining, and surface treatment; all these fabrication stages make the final product expensive [1][2][3]. Powder metallurgy (PM) processing offers an interesting alternative for many applications since it provides near-net-shape parts [1], enhancing the flexibility of design, minimizing the machining steps, and increasing the material yield.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, processing of titanium powders to give final components by the conventional pressing and sintering route requires sintering temperatures around 1200-1400 • C employing long dwell times (2 to 5 h typically) which suppose high energy consumption. Hence, there is room to reduce processing cost by means of alternative routes or using alternative starting powders and alloying elements that help to improve the sintering parameters maintaining the final properties, in terms of density and microstructure [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 is the original titanium powder morphology, and Table 1 is the powder composition. Metal powder is the key raw material for powder metallurgy, and its quality largely determine the final moulding effect and comprehensive performance of powder metallurgy products [20]. The apparent density and flowability of the original Ti powder were tested by Hall flow-meter.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the predicted value of flow stress (σp) could be obtained by Equation (13). The value of Z could be calculated by Equation (10):…”
Section: Arrhenius-type Constitutive Modelingmentioning
confidence: 99%
“…Some researchers consider Fe a promising substitution for V in α + β titanium alloys due to its relatively low cost and strong BCC phase stablishing ability [ 8 , 9 ]. It was reported that the addition of Fe could also help to enhance the sinterability of PM titanium components, thanks to its high diffusion rate in Ti [ 10 , 11 , 12 ]. On the other hand, the local segregation of Fe particles and the formation of a brittle TiFe phase could be prevented in the solid sintering process [ 13 ].…”
Section: Introductionmentioning
confidence: 99%